Risk Management Practices in Small and Medium Enterprises in Morocco: A Study of Performance - GARTİ, OMAR (İstanbul Kültür Üniversitesi, 2024)
Small and Medium-Sized Businesses (SMEs) are able to quickly adjust to changes in the economy and satisfy customer needs because of their distinctive structural flexibility. This adaptability can cause SMEs to grow quickly and become big, powerful businesses, or it can cause them to fail soon after they are founded. With SMEs accounting for an astounding 93% of all firms in Morocco, they are considered the backbone of the country's economy. These businesses, despite their importance, are exposed to many risks related to money, economic growth, and the environment that may jeopardize their long-term viability. Because they frequently lack a thorough risk management culture, SMEs are more susceptible to these hazards than their larger counterparts. The purpose of this study is to give a comprehensive evaluation of risk management procedures used by Moroccan SMEs. It examines the main risks that these businesses face and assesses how well-managed those risks are now. The study aims to shed light on the variables influencing the adoption of operational risk management systems by identifying the major hazards affecting SMEs. Moreover, it investigates how these methods might affect Moroccan SMEs' financial performance, especially during recessionary times. Our objective of conducting this research is to raise awareness of how crucial it is for SMEs to have efficient risk management. The study is to contribute to the creation of strong risk management frameworks that can improve the resilience and financial stability of Moroccan SMEs by comprehending the difficulties and finding best practices. This will support their critical role in the country's economy by reducing risks and maximizing chances for development and sustainability.
Fas'ta Küçük ve Orta Ölçekli Şirketlerde Risk Yönetimi Uygulamaları: Bir Performans Çalışması
Yüksek lisans tezi.
Keywords: Risk; Risk Management; Small-Medium Enterprises; Performance